New “design” of human capital management in a flexible employment (Journal of Economic Research & Business Administration, 2021)
The labor market is constantly changing, atypical work is gaining significant relevance, especiallyin the current time of restrictions associated with the coronavirus crisis. In Kazakhstan, the promotionof a teleworking law has made flexibility in work an interesting topic and has become an increasinglyimportant requirement in hiring and a motivating factor for employees. In this context, this article aims toexplore the relationship between employee development and flexibility in working time and workspaceas important characteristics of sustainable management of human capital, job satisfaction and employeeproductivity. In addition, the article is aimed at studying the impact on the performance of employeesof various types of flexibility – contractual, functional, working time and workspace flexibility. To emphasizethe relevance of employee development and employee flexibility as important aspects of sustainablehuman capital management. To make this possible, a “Composite Employee Flexibility Score”was developed, which considers different types of flexibility, based on employee feedback collectedthrough a nationally representative survey using multiple match analysis. In addition, the effect of individualflexibility and employee flexibility on overall job satisfaction was quantified using binary logisticregression models. The study reveals the concept of “work flexibility”, special attention is paid to theimpact of new types of workspaces (flexible office, coworking, shared home office, partial home office)on labor productivity, job satisfaction, organizational efficiency, professional growth and development, social and professional relationships, personal professional activities, as well as the general level of workmotivation.Key words: flexible management of human capital, methodology of agile HC management, projectmanagement of HC, flexibility of work, job satisfaction.